Fe toxicity in plants: Impacts and remediation - Zahra, Noreen; Hafeez, Muhammad Bilal; Shaukat, Kanval; Wahid, Abdul; Hasanuzzaman, Mirza (Physiologia plantarum, 2021)
Fe is the fourth abundant element in the earth crust. Fe toxicity is not often discussed in plant science though it causes severe morphological and physiological disorders, including reduced germination percentage, interferes with enzymatic activities, nutritional imbalance, membrane damage, and chloroplast ultrastructure. It also causes severe toxicity to important biomolecules, which leads to ferroptotic cell death and induces structural changes in the photosynthetic apparatus, which results in retardation of carbon metabolism. However, some agronomic practices like soil remediation through chemicals, nutrients, and organic amendments and some breeding and genetic approaches can provide fruitful results in enhancing crop production in Fe‐contaminated soils. Some quantitative trait loci have been reported for Fe tolerance in plants but the function of underlying genes is just emerging. Physiological and molecular mechanism of Fe uptake, translocation, toxicity, and remediation techniques are still under experimentation. In this review, the toxic effects of Fe on seed germination, carbon assimilation, water relations, nutrient uptake, oxidative damages, enzymatic activities, and overall plant growth and development have been discussed. The Fe dynamics in soil rhizosphere and role of remediation strategies, that is, biological, physical, and chemical, have also been described. Use of organic amendments, microbe, phytoremediation, and biological strategies is considered to be both cost and environment friendly for the purification of Fe‐contaminated soil, while to ensure better crop yield and quality the manipulation of agronomic practices are suggested.